Kinesiology terminology in Croatian sign language - Vuljanić, Ana; Tišma, Dragana; Naumovski, Angel (2020)
The kinesiological areas of education, sport, sports recreation and kinesitherapy of children and youth with hearing impairment present a methodological and didactical problem, which occurs due to the specific characteristics that people with hearing impairment possess. The communication aspect of the work with children and youth with hearing impairment is considerably limited. Therefore, to ensure an optimal and continuous kinesiological process, it is important to know all the specificities of working with them. The main goal of this paper is to outline some general recommendations and adjustments related to the work with children and youth with hearing impairment in kinesiological areas. Special attention will be given to the communication systems and the presentation of kinesiological terminology in the Croatian sign language in order to optimize the communication aspect. This professional paper is an introduction to a more comprehensive manual on the specifics of children and youth with hearing impairment in the motor environment, specialties of kinesiological education, with the addition of general recommendations and adaptations for work and a wider presentation of kinesiological terminology in the Croatian sign language. The basic knowledge on the methodological, didactic and communication approach to children and youth with hearing impairment in the field of kinesiological education, as well as other kinesiological orientations will be given to the educators, teachers and professors who are not sufficiently informed and adequately educated in this field during their studies, as well as to the current students of the same orientations.
Bibliografija: 13 jed.
Summary.
Keywords: Kineziologija -- Terminologija -- Obrazovanje -- Osobe s oštećenjem sluha -- Znakovni jezik